Penaeus monodon Shell Powder Extract as A Candidate for Dental Material Restoration - Moh Basroni Rizal; Widyasri Prananingrum; Dian Widya Damaiyanti (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
The prevalence of dental caries in Indonesia is still high. One of the dental caries treatments is direct restoration. Biomaterial, often used as a restorative material, is glass ionomer cement which has a silica content of 35%. Silica is found in Penaeus monodon shells which have been a waste of production. This research aims to study the characteristic of Penaeus monodon shell powder extracts as candidates for dental materials restoration. The research sample used was Penaeus monodon shell powder extract which was then carried out by a depigmentation process by mixing acetone 1:10 (w/v) ≤ 20 hours. Samples were tested with the XRD test (x-ray diffraction). SEM assessment was performed to evaluate the morphology of the particle. Data were analyzed using Mann-Whitney. The result demonstrated a significant silica content in Penaeus monodon shell powder extract before and after the depigmentation process with a p-value of 0,00 (p0,05). The depigmentation process can decrease silica content in Penaeus monodon shell powder extract. There was a different comparison of silica content in Penaeus monodon shell powder extract before and after depigmentation as a candidate for dental materials restoration.